Agile Software Development Techniques: A Survey: Agile Software Development Techniques: A Survey - Nawaz, Marriam; Nazir, Tahira; Islam, Seema; Masood, Momina; Mehmood, Awais; Kanwal, Samira (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
In this IT era, where there is a race of software development, it is necessary to introduce such types of software development techniques which will help the practitioners to deliver fast solutions. In the past, various traditional approaches were used for this purpose, but now agile techniques are getting more popular because conventional software development approaches are not efficient in managing the changing requirements. The agile software development process is one of the most emerging lightweight software development methodologies, which uses iterative and prototype development approaches to accommodate changes in software requirements. Final software products are delivered to the end-users in short iterations. One of the most noticeable drawbacks of agile methods is their limited courtesy to the structured and architectural design of the system. Hence this development approach will restrict small to medium design decisions only. In this paper, we have performed the analysis of different agile techniques, which will help the readers to understand their positive and negative points and select the most appropriate technique suited to their projects.